Adverse effects of autoclaved diets on the progression of chronic kidney disease (CKD) and CKD-Mineral Bone Disorder in rats - Biruete, Annabel (Am J Nephrol, 2020)
BACKGROUND: Autoclaving rodent diets is common in laboratory animals, but autoclaving increases the formation of dietary advanced glycation end-products (AGEs). We studied the effect of autoclaved diet alone or in combination with a diet high in bioavailable phosphorus on biochemistries of chronic kidney disease-mineral and bone disorder (CKD-MBD), intestinal gene expression, and oxidative stress. METHODS: Male CKD rats (Cy/+) and normal littermates (NL) were fed 1 of 3 diets: autoclaved 0.7% phosphorus grain-based diet for 28wks (AC); autoclaved diet for 17wks followed by non-autoclaved 0.7% phosphorus casein diet until 28wks (AC+Casein); or non-autoclaved diet for 16wks followed by a non-autoclaved purified diet until 30wks (Non-AC+Casein). RESULTS: Autoclaved diets contained ~3x higher AGEs and levels varied depending on the location within the autoclave. Rats fed the AC and AC+Casein diets had higher total AGEs and oxidative stress, irrespective of kidney function. Kidney function was more severely compromised in CKD rats fed AC or AC+Casein compared to Non-AC+Casein. There was a disease-by-diet interaction for plasma phosphorus, PTH, and c-terminal FGF23, driven by high values in the CKD rats fed the AC+Casein diet. Compared to Non-AC+Casein, AC and AC+Casein-fed groups had increased expression of receptor of AGEs (RAGE) and intestinal NADPH oxidase DUOX2, independent of kidney function. CONCLUSIONS: Autoclaving rodent diets impacts the progression of CKD and CKD-MBD, highlighting the critical importance of standardizing diets in experiments.